Prevalence of actinic keratosis among dermatology outpatients in Austria. (19th November 2014) - Eder, J.; Prillinger, K.; Korn, A.; Geroldinger, A.; Trautinger, F.
<x xml:space="preserve">Abstract</x> What's already known about this topic? AKs are common precursor lesions of SCC with prevalence data originating mostly from Australia and the U.S.A. What does this study add? In Austria, one‐third of dermatology outpatients have AK. Chronically sun‐exposed body sites of older men are particularly affected. Adult dermatology outpatients are a suitable target population for AK screening, treatment and prevention.